Cancer Risk after Fat Transfer: A Multicenter Case-Cohort Study. Issue 1 (January 2017) - Myckatyn, Terence M.; Wagner, I. Janelle; Mehrara, Babak J.; Crosby, Melissa A.; Park, Julie E.; Qaqish, Bahjat F.; Moore, Dominic T.; Busch, Evan L.; Silva, Amanda K.; Kaur, Surinder; Ollila, David W.; Lee, Clara N.
Abstract : Background: Fat transfer is an increasingly popular method for refining postmastectomy breast reconstructions. However, concern persists that fat transfer may promote disease recurrence. Adipocytes are derived from adipose-derived stem cells and express adipocytokines that can facilitate active breast cancer cells in laboratory models. The authors sought to evaluate the association between fat transfer to the reconstructed breast and cancer recurrence in patients diagnosed with local or regional invasive breast cancers. Methods: A multicenter, case-cohort study was performed. Eligible patients from four centers (Memorial Sloan Kettering, M. D. Anderson Cancer Center, Alvin J. Siteman Cancer Center, and the University of Chicago) were identified by each site's institutional tumor registry or cancer data warehouse. Eligibility criteria were as follows: mastectomy with immediate breast reconstruction between 2006 and 2011, age older than 21 years, female sex, and incident diagnosis of invasive ductal carcinoma (stage I, II, or III). Cases consisted of all recurrences during the study period, and controls consisted of a 30 percent random sample of the study population. Cox proportional hazards regression was used to evaluate for association between fat transfer and time to recurrence in bivariate and multivariate models. Results: The time to disease recurrence unadjusted hazard ratio for fat transfer was 0.99 (95 percent CI, 0.56 to 1.7). After adjustment for age, body mass index, stage, HER2/Neu receptor status, and estrogen receptor status, the hazard ratio was 0.97 (95 percent CI, 0.54 to 1.8). Conclusion: In this population of breast cancer patients who had mastectomy with immediate reconstruction, fat transfer was not associated with a higher risk of cancer recurrence. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.